Widespread metachronous carcinoid tumour metastases to the head and neck: a unique presentation. Issue 9 (November 2016) - Koraitim, Mohamed; Spedding, Anne V.; Bradley, Katy; Brennan, Peter A.
Abstract: Carcinoid tumours are usually slow-growing, neuroendocrine neoplasms that primarily affect the gastrointestinal tract and bronchial tree. Although relatively rare, isolated, single metastasis to the head and neck has been reported. We present a unique case of 6 metachronous carcinoid metastases to both parotid glands, the left submandibular gland, upper lip, and thyroid, over 3 years. To our knowledge, this widespread presentation in the head and neck has not previously been reported.